Attachment comes of age: adolescents' narrative coherence and reflective functioning predict well-being in emerging adulthood. Issue 4 (4th July 2019) - Borelli, Jessica L.; Brugnera, Agostino; Zarbo, Cristina; Rabboni, Massimo; Bondi, Emi; Tasca, Giorgio A.; Compare, Angelo
ABSTRACT: This study investigated the effects of adolescents' attachment security and reflective functioning (RF) (assessed by the adult attachment interview [AAI]) in the prediction of well-being in adulthood. Adolescents ( N  = 79; M  = 14.6 years old; SD = 3.5 years) completed the AAI at Time 1 (T1), which was subsequently coded for inferred attachment experiences, narrative coherence, and RF by three nonoverlapping teams of raters. Participants completed the Psychological General Well-being Index at T1 and 8 years later (Time 2, T2). Analyses showed that (a) both adolescent narrative coherence and RF were significant predictors of almost all indices of well-being at T2 in adulthood; (b) both narrative coherence and RF indirectly linked inferred loving parental care and T2 well-being; (c) when included in the same model, RF was a significant indirect effect linking inferred loving parental care and T2 well-being. These findings contribute to theory in suggesting that both RF and narrative coherence are predictive of subsequent psychological well-being and operate as links between inferred parental care and subsequent adjustment. Possible mechanisms underlying these findings are discussed.